Analisis Kapasitas Produksi dan Permintaan pada UMKM Nira Gitar - Niki Nivolini; Muhammad Syihabuddin (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
The creative industry sector, particularly the musical instrument craft, is showing a positive growth trend due to the increasing interest in music among the public. However, this rising demand often does not match the production capacity of small and medium enterprises (UMKM). This study aims to analyze the production capacity and demand patterns of Nira Gitar, a UMKM located in Klaten, Central Java. Using a descriptive qualitative approach, data was collected through in depth interviews with the owner and employees, field observations, and sales reports from January to December 2025. The findings show that Nira Gitar has an average monthly production capacity of 50 guitar units, with each unit taking 2 to 3 days to complete. This capacity is limited by several key factors, namely the use of manual production tools, a shortage of experienced workers, fluctuations in the availability of high-quality wood materials (mahogany and meranti), and weather conditions affecting the drying process. On the other hand, the total demand for the year 2025 reached 598 units, with the highest order recorded in December, totaling 118 units. The company's strategy of educating customers about the product and focusing on quality rather than quantity has built consumer trust, even though the production capacity is not yet able to meet market demand instantly. This study recommends the need for gradual modernization of production tools, training for workers' skills, and strengthening the supply chain of raw materials to improve efficiency and production volume in order to meet the continuously growing market demand.